Establishing benchmarks for assessing early mathematical competence in children - Menacho, Inmaculada; Aragón, Estívaliz; Arrigoni, Flavia; Mera, Carlos; Canto, M. Carmen; Navarro, Jose I. (Frontiers in Education, 2024)
The Early Numeracy Test-Revised (ENT-r) development was followed by several provisional standardization processes to adapt to this new version. Subsequently, the ENT-r underwent translation into Spanish and a shift from a paper-and-pencil format to a computerized version, intending to make it accessible online for schools. This paper introduces the adapted Spanish version of ENT-r and outlines the provisional standardization procedure conducted with a group of Spanish children. In this initial pilot study, 141 children aged between 4 and 7 underwent individual assessments. Among them, 71 were girls (50.3%), and 70 were boys (49.6%). Selected from three public schools in a middle-class area, the children were evaluated by experienced researchers with expertise in assessing young children. The study involved three provisional statistical analyses using ENT-r data. Initially, a descriptive analysis was conducted, followed by a cross-age score comparison to assess scores across different age groups. Finally, a reliability study was performed. Preliminary results from these analyses indicate that the ENT-r demonstrates reliability, and its items effectively discriminate between prerequisite and counting tasks. Finally, an approximate statistical estimation was carried out regarding the level of mathematical competence, which is one of the parameters provided by the test, allowing the development of alternative improvement programs for the less prominent values.